Typology of birth centres in the Netherlands using the Rainbow model of integrated care: results of the Dutch Birth Centre Study - Inge C. Boesveld; Marc A. Bruijnzeels; Marit Hitzert; Marieke A. A. Hermus; Karin M. van der Pal-de Bruin; M. E. van den Akker-van Marle; Eric A. P. Steegers; Arie Franx; Raymond G. de Vries; Therese A. Wiegers (BMC, 2017)
Abstract Background The goal of integrated care is to offer a continuum of care that crosses the boundaries of public health, primary, secondary, and tertiary care. Integrated care is increasingly promoted for people with complex needs and has also recently been promoted in maternity care systems to improve the quality of care. Especially when located near an obstetric unit, birth centres are considered to be ideal settings for the realization of integrated care. At present, however, we know very little about the degree of integration in these centres and we do not know if increased levels of integration improve the quality of the care delivered. The Dutch Birth Centre Study is designed to evaluate birth centres and their contribution to the Dutch maternity care system. The aim of this particular sub-study is to classify birth centres in clusters with similar characteristics based on integration profiles, to support the evaluation of birth centre care. Methods This study is based on the Rainbow Model of Integrated Care. We used a survey followed by qualitative interviews in 23 birth centres in the Netherlands to determine which integration profiles can be distinguished and to describe their discriminating characteristics. Cluster analysis was used to classify the birth centres. Results Birth centres were classified into three clusters: 1)"Mono-disciplinary-oriented birth centres" (n = 10): which are mainly owned by primary care organizations and established as physical facilities to provide an alternative birthplace for low risk births; 2) "Multi-disciplinary-oriented birth centres" (n = 6): which are mainly multi-disciplinary oriented and can be regarded as facilities to give birth, with a focus on integrated birth care; 3) "Mixed Cluster of birth centres" (n = 7): which have a range of organizational forms that differentiate them from centres in the other clusters. Conclusion We identified a recognizable classification, with similar characteristics between birth centres in the clusters. The results of this study can be used to relate integration profiles of birth centres to quality of care, costs, and perinatal outcomes. This assessment makes it possible to develop recommendations with regard to the type and degree of integration of Dutch birth centres in the future.